Modeling neuromuscular diseases in zebrafish - Singh, Jaskaran; Patten, Shunmoogum A. (Frontiers in Molecular Neuroscience, 2022)
Neuromuscular diseases are a diverse group of conditions that affect the motor system and present some overlapping as well as distinct clinical manifestations. Although individually rare, the combined prevalence of NMDs is similar to Parkinson's. Over the past decade, new genetic mutations have been discovered through whole exome/genome sequencing, but the pathogenesis of most NMDs remains largely unexplored. Little information on the molecular mechanism governing the progression and development of NMDs accounts for the continual failure of therapies in clinical trials. Different aspects of the diseases are typically investigated using different models from cells to animals. Zebrafish emerges as an excellent model for studying genetics and pathogenesis and for developing therapeutic interventions for most NMDs. In this review, we describe the generation of different zebrafish transgenic models mimicking NMDs and how they were used for drug discovery and therapy development.